Development of an objective evaluation framework with subjective impact - Taylor, J. P. (Cranfield University, 1999)
Multimedia technologies are finding new and advanced uses within the modern organisation. From a strategic perspective, these organisations realise techhology contributes to enhance productivity and operational success. However, to embrace technology without recourse to those who ultimately utilise such facilities, could effectively jeopardize the up-take of new improved working practices. Sir Paul Condon: Commissioner of Police for the Metropolis has been noted within MetView (1999) for the following statements: • “Technology is playing an ever increasing role in modern policing methods and has been responsible for many of our current successes” • "Good and innovative policing, and good and innovative technology cannot be separated”. To continue this success there is a need within a modern policing organisation to develop an objective framework for evaluating multimedia technologies. This framework will give recognition to subjective user issues that are necessary to contribute towards the partnership that exists between innovative policing and innovative technology. This research presents a framework that achieves specific business requirements outlined by a technology aware department within a police organisation. Three research objectives were completed. These objectives are: - Provide a business process for evaluating multimedia technologies in a way that is repeatable and unbiased - Provide a sound foundation that accounts for the typical user of multimedia technologies - Aid towards increased user satisfaction and confidence. Conclusions detail the objective evaluation framework with subjective impact, reference to a business process and considerations for a modern policing organisation on a way forward